Persepsi Ibu Bayi atau Ibu Balita terhadap Posyandu (Studi Kualitatif Pendekatan Fenomenologi) - Norfai Norfai; Eddy Rahman; Abdullah Abdullah (Jurnal Akademika Baiturrahim Jambi, 2021)
This research is a qualitative research with a phenomenological approach. Determining the number of informants used in qualitative research consists of two considerations, namely suitability and adequacy. The suitability in this case is that the researcher uses purposive sampling, where the researcher determines the informant according to the criteria, which means that the informant is able to provide information in accordance with the research objectives. Adequacy refers to the number of informants consisting of 5 to 8 participants, with a note that there are no more significant variations in answers from one source to another data source or saturation, if it does not reach saturation, then the selection of informants will continue. The data was collected by means of in-depth interviews using interview guidelines consisting of open-ended questions and a voice recorder as a tool to record all information that has been conveyed by the informants. Data processing and analysis were carried out by transcription, finding keywords, creating categories, grouping categories into sub-themes, formulating themes and continued by integrating the results of the analysis into descriptive form. Still not fully understanding about the posyandu program, it is necessary to strengthen the role of posyandu cadres by conducting intensive coaching and there needs to be adequate incentives for cadres in an effort to increase the cadres' motivation